Analysis of Factors Affecting CD4+ Increase in HIV / AIDS Patients Receiving ARV Therapy (Universitas Negeri Semarang, 2021)
Acquired immunodeficiency syndrome (AIDS) is a collection of symptoms and infections that arise due to damage to the human immune system due to infection with the Human Immunodeficiency Virus (HIV). The number of HIV patients at Panti Wilasa Hospital continues to increase from every year in 2018 the number is 150 HIV / AIDS patients. The purpose of this study was to analyze the factors that influence the increase in CD4+ levels of HIV / AIDS patients receiving ARV therapy at Panti Wilasa Citarum and Dr. Cipto Hospitals Semarang. This research is a quantitative study, with a cross-sectional approach. The minimum sample of the study was 38 respondents using simple random sampling technique. Data analysis in this study using Multiple Logistic Regression. The results of the study, the most influential variables were clinical stage (p=0.000), and concomitant disease tuberculosis (p = 0.14) on the increase in CD4+ levels. The risk of HIV / AIDS transmission in Indonesia is the highest and until now, there is no cure for HIV. ARV therapy can inhibit the development of the HIV virus, giving ARVs is given if the CD4+ level is less than 500 cells / mm3, or there are other conditions in HIV patients. The importance of early awareness in ARV therapy for early initiation of ARVs is proven to be clinically beneficial, useful for prevention, increase life expectancy and reduce the incidence of HIV-related infections.